The Humanistic and Economic Burden Associated with Anxiety and Depression among Adults with Comorbid Diabetes and Hypertension - Kimberly Wallace; Xiaohui Zhao; Ranjita Misra; Usha Sambamoorthi (Journal of Diabetes Research)
We conducted a retrospective cross-sectional study to estimate the humanistic and economic burden associated with depression and anxiety among adults with comorbid diabetes and hypertension. Pooled data from the 2013 and 2015 Medical Expenditure Panel Survey were used to include adults (≥18 years old) who were alive and diagnosed with both diabetes and hypertension during the observation period. We assessed the humanistic burden with health-related quality of life (HRQoL) and economic burden with the total annual healthcare expenditures. Depending on the presence/absence of depression and anxiety, the study sample was divided into four groups (i.e., no depression/anxiety, depression only, anxiety only, and depression and anxiety). Multivariable regression analyses were used to evaluate the associations between the depression/anxiety categories and disease burden measures. The incremental burden associated with depression and/or anxiety was estimated with the counterfactual recycled prediction. Of the 4560 adults with comorbid diabetes and hypertension, 13.2% reported depression only, 8.7% reported anxiety only, and 7.7% reported both. Results from adjusted analyses indicated that the presence/absence of depression and anxiety was associated with significantly poorer HRQoL, especially on the mental component. Having either depression or anxiety corresponded to reduced mental component summary scores by more than four points. The reduction was as high as 10.35 points when both conditions occurred. Comparing to adults without depression or anxiety, the per-capital incremental annual healthcare expenditures were $4607 for the depression group, $2481 for the anxiety group, and $8709 for adults with both conditions. Furthermore, adults with depression and anxiety were 58% more likely to spend at least 10% of annual household income on healthcare as compared to those with neither the conditions. Our results highlight the needs for integrating cost-effective mental health services into diabetes management to improve the HRQoL and reduce healthcare costs for adults with comorbid diabetes and hypertension.